Penyusunan dan Pelaksanaan Anggaran dalam Konteks Pengembangan Usaha (Studi pada Bakso dan Mie Ayam Mas Hadi "Asli Solo") - Agustin, Devi; Ismanto, Bambang; Sitorus, Destri Sambara (Jurnal Samudra Ekonomi dan Bisnis, 2021)
The budget presents information about expenditure and income plans expressed in rupiah units for the coming period. This study aims to analyze the process of preparing and implementing the budget in developing the business of Meatballs and Chicken Noodles Mas Hadi “Asli Solo". This qualitative-descriptive research was collecting data through observation, documentation and interviews. Data analysis was carried out through the stages of reduction, display and data verification. To increase the confidence (triangulation) of data, a repeat research and cross-check of research sources was conducted. The results showed that the purpose of business development was carried out to introduce the product to the community and obtain as much profit as possible. There are several stages of preparation and implementation process of budget in the context of business development that are appropriate, but some are not yet in accordance with. Budget components of the research object include place, equipment and supplies